The Measurement of Economic Entities Performance from the Non Financial Indicators’ Perspective: Array - ibranisteanu, Delia – Mihaela (Acta Universitatis Danubius. Œconomica, 2020)
Since the financial performance was on the first rank in the past, nowadays the economic entities are increasingly aware that it only offers them the consequence of the analysis of financial indicators. There is tackled a new given value of performance, namely the global performance, taking into account the extension to social and environmental indicators. The success of an entity involves assembling economic, social and environmental performance. Most economic entities aspire to success because the performance management has become a work process not only useful but also mandatory, and it couldn’t have achieved the desired success without a proper management. In this situation the performance assessment represents the basic element.